Pengaruh Pengembangan Karir, Kompensasi dan Motivasi terhadap Kinerja Karyawan pada Moena Fresh di Denpasar - Pradnyani, Gusti Ayu Supastini; Sadiartha, A.A Ngurah Gede; Gede, I Komang (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The aim of this study is to assess how career development, compensation, and motivation impact The aim of this study is to investigate how career advancement, compensation, and motivation impact the performance of employees at Moena Fresh Denpasar. Thirty-two respondents participated in this research. Several analytical methods were utilized, such as assessing validity, analyzing reliability, evaluating classical assumptions, conducting multiple linear regression, analyzing coefficient of determination, performing T-tests, and conducting F-tests.. The findings indicate that career advancement positively influences employee performance, as does compensation and motivation. Furthermore, when considering all three factors simultaneously, they collectively demonstrate a significant impact on employee performance. These variables jointly contribute to 65% of the variance in employee performance. Recommendations stemming from this study include incentivizing employees who meet targets, providing consistent training opportunities, establishing incentive structures commensurate with employee achievement levels, and consistently recognizing outstanding employee performance at Moena Fresh Denpasar